1998
DOI: 10.1161/01.str.29.12.2649
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Magnetic Resonance Imaging in a Case of Cerebral Venous Thrombosis

Abstract: Background-Diffusion-weighted imaging (DWI) is the most sensitive MR sequence in acute arterial ischemic stroke buthas not yet been evaluated in venous cerebral ischemia. We describe a patient with DWI performed at the acute phase of a venous ischemic stroke. Case Description-A rapid cerebral MRI including DWI and fast fluid-attenuated inversion recovery (FLAIR) sequences was performed at the acute phase of a venous stroke confirmed by conventional angiography. DWI showed a slight decrease in apparent diffusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
31
0
3

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 22 publications
5
31
0
3
Order By: Relevance
“…When observed with DWI, the ADC values in vasogenic edema are increased, 8 as in our patient. A similar case was recently published by Corvol et al, 9 who found slight, reversible DWI and marked fluid-attenuated inversion recovery abnormalities in a patient with CVT of the superior sagittal sinus and flow reversal in the cortical veins. The findings were judged to be vasogenic edema; the patient recovered rapidly after treatment with intravenous heparin and had a complete normalization of ADC values.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…When observed with DWI, the ADC values in vasogenic edema are increased, 8 as in our patient. A similar case was recently published by Corvol et al, 9 who found slight, reversible DWI and marked fluid-attenuated inversion recovery abnormalities in a patient with CVT of the superior sagittal sinus and flow reversal in the cortical veins. The findings were judged to be vasogenic edema; the patient recovered rapidly after treatment with intravenous heparin and had a complete normalization of ADC values.…”
Section: Discussionsupporting
confidence: 80%
“…The induced venous infarction was characterized by perfusion deficits and early cytotoxic edema (ADC declined to 56Ϯ7%) closely followed by vasogenic edema after blood-brain barrier disruption (ADC, 84Ϯ8% by 48 hours). This animal study proves that venous infarction with damage of neuronal tissue can be predicted by typical patterns in DWI and PI, which are known from arterial stroke and are more severe than in the case presented in this article and the case of Corvol et al 9 In conclusion, we believe that in addition to their use for evaluation of ischemic stroke after arterial vessel occlusion, DWI and PI can play a role in diagnosis of cerebral venous ischemia. The MR features presented in this case reflect the underlying pathophysiology of venous congestion with impaired but viable neuronal tissue.…”
Section: Discussionsupporting
confidence: 77%
“…Diffusion weighted images may not offer information regarding the establishment of diagnosis but provide information on the pathophysiology of CVST. 14,15,49,72 Transcranial Doppler ultrasonography offers a noninvasive approach for diagnosis or follow-up of CVST, but the results are not sufficient for providing a valuable tool in the clinical setting.…”
mentioning
confidence: 99%
“…[38][39][40][41][42][43] In a review of cranial sinus thrombosis cases from 1942 to 1990, Diaz et al 43 showed this combination to be particularly lethal, resulting in a mortality rate of 95.6%. In these patients, pulmonary embolism appeared to be strongly suggestive of thrombus dislodgment from the cranial sinuses, particularly the superior sagittal sinus.…”
Section: Devicesmentioning
confidence: 99%